3D angle-independent Doppler and speckle tracking for the myocardium and blood flow. Issue 4 (December 2019) - McDicken, Norman; Thomson, Adrian; White, Audrey; Toor, Iqbal; Gray, Gillian; Moran, Carmel; Watson, Robin J; Anderson, Tom
Abstract : A technology based on velocity ratio indices is described for application in the myocardium. Angle-independent Doppler indices, such as the pulsatility index, which employ velocity ratios, can be measured even if the ultrasound beam vector at the moving target and the motion vector are not in a known plane. The unknown plane situation is often encountered when an ultrasound beam interrogates sites in the myocardium. The velocities employed in an index calculation must be close to the same or opposite directions. The Doppler velocity ratio indices are independent of angle in 3D space as are ratio indices based on 1D strain and 1D speckle tracking. Angle-independent results with spectral Doppler methods are discussed. Possible future imaging techniques based on velocity ratios are presented. By using indices that involve ratios, several other sources of error cancel in addition to that of angular dependence for example errors due to less than optimum gain settings and beam distortion. This makes the indices reliable as research or clinical tools. Ratio techniques can be readily implemented with current commercial blood flow pulsed wave duplex Doppler equipment or with pulsed wave tissue Doppler equipment. In 70 patients where the quality of the real-time B-mode looked suitable for the Doppler velocity ratio technique, there was only one case where clear spectra could not be obtained for both the LV wall and the septum. A reproducibility study of spectra from the septum of the heart shows a 12% difference in velocity ratios in the repeat measurements.